Comparison of Community Life in the Legend of Puyang Perahu Kawah and the Short Story Dua Wajah Ibu by Guntur Alam: A Sociological Analysis of Literature - Alvionita, Elica (Centre for Literary and Cultural Studies, 2024)
This study aims to compare the representation of life during the colonial and modern eras in literary works through a sociology of literature approach, focusing on the legend of